Microfinance and sustainable development of MSMEs and entrepreneurs in Serbia - Ostojic, Ivana (Industrija, 2024)
The focus of the study is the analysis of the potential benefits for the growth and sustainable development of micro, small and medium enterprises (MSMEs) and entrepreneurs that would arise from the improvement of the domestic financial system through the introduction and representation of microfinance institutions. The study has been conducted on a sample of 150 respondents from the banking and private sector. Data analysis has been performed by a non-parametric method, the chi-square χ2 test of independence. Statistical data processing is performed using the statistical software package IBM SPSS Statistics 21. Results of the study indicate that the domestic financial system is banking-centric, undeveloped, poor and does not encourage sustainable development and growth of micro, small and medium enterprises and entrepreneurs. Also, the research confirmed that the introduction of microfinance institutions would contribute to the improvement of the domestic financial system, the establishment of micro, small and medium enterprises and entrepreneurs, as well as their positive business performance results and sustainable development.
Keywords: microfinance, micro, small and medium enterprises, entrepreneurs, sustainability, bank-centric financial system, Serbia.